A tile service-driven architecture for online climate analysis with an application to estimation of ocean carbon flux. (August 2019) - Ye, Weiwen; Zhang, Feng; Bai, Yan; Du, Zhenhong; Liu, RenYi
Abstract: The deteriorating environmental system and increasing number of time-varying datasets have generated a significant demand for new techniques to support online high-efficiency climate analysis. In response to this demand, this paper introduces an innovative multilayer architecture driven by a tile service in a virtual globe environment. This architecture is supported by the open-source and highly efficient osgEarth virtual globe. In addition, we develop a gSoap-based tile service to address the challenges of visualizing and analysing massive data under hardware restrictions conditions. The service contains a lossless pyramid tile set that can automatically provide tiles with proper accuracy according to the demands of users under different conditions. Furthermore, we add a hybrid database file system to the service for high availability. This service is then applied for estimation of ocean carbon flux. And a proof-of-concept prototype, SatCO2, has been developed to demonstrate the feasibility and performance of the proposed architecture. Highlights: Various GIS methods were incorporated into the innovative multilayer architecture. The architecture realizes the rapid display of massive data on the 3D virtual globe under a limited network bandwidth. The architecture provides efficient statistical analysis for high concurrency requests under restricted hardware conditions. The architecture is more effective than traditional methods.